Numerical Fluid Modelling of the Plasma Edge Response to a 3D Object and Application to Mach Probe Measurements. Issue 4 (June 2014) - Paredes, A.; Serre, E.; Schwander, F.; Ghendrih, Ph.; Tamain, P.
Abstract The penalization method Ref. [1] is used to model the interaction of 3D probe with an isothermal plasma. Density maps show that the region perturbed by the obstacle, is not restricted to its near neighbourhood, but can extend to the whole SOL. In the particular case of a probe, which is used to measure local plasma parameters, this impact can lead to violation of assumptions of locality of the perturbation usually used in determining Mach number from the imbalance in density on both sides of the probe. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)